Germline heterozygous variants in genes associated with familial hemophagocytic lymphohistiocytosis as a cause of increased bleeding. (2nd January 2018) - Fager Ferrari, Marcus; Leinoe, Eva; Rossing, Maria; Norström, Eva; Strandberg, Karin; Steen Sejersen, Tobias; Qvortrup, Klaus; Zetterberg, Eva
Abstract: Familial hemophagocytic lymphohistiocytosis (FHL) is caused by biallelic variants in genes regulating granule secretion in cytotoxic lymphocytes. In FHL3–5, the affected genes UNC13D, STX11 and STXBP2 have further been shown to regulate the secretion of platelet granules, giving rise to compromised platelet function. Therefore, we aimed to investigate platelet degranulation in patients heterozygous for variants in UNC13D, STX11 and STXBP2 . During the work-up of patients referred to the Coagulation Unit, Skåne University Hospital, Malmö, Sweden and the Department of Hematology, Rigshospitalet, Copenhagen, Denmark due to bleeding tendencies, 12 patients harboring heterozygous variants in UNC13D, STX11 or STXBP2 were identified using targeted whole exome sequencing. Transmission electron microscopy (TEM) was used to assess the secretion of platelet dense granules following thrombin stimulation. Platelet degranulation, activation and aggregation were further assessed by flow cytometry (FC) and light transmission aggregometry (LTA) with lumi-aggregometry. In total, eight out of twelve (67%) patients showed impaired degranulation by at least one of the assays (TEM, FC and LTA). In the 12 patients, eight different heterozygous variants were identified. One variant was strongly associated with impaired degranulation, while four of the variants were associated with impaired granule secretion to a slightly lesser extent. One additional variant was found in six out of the twelve patients, and was associated with varying degrees of degranulation impairment. Accordingly, six out of the eight (75%) identified variants were associated with impaired platelet degranulation. Our results suggest that heterozygous variants in UNC13D, STX11 and STXBP2 are sufficient to cause platelet secretion defects resulting in increased bleeding.